Les « déportés » de la Creuse : le dévoilement d’une histoire oubliée - Valérie Magdelaine-Andrianjafitrimo (Itinéraires)
The scandal surrounding the “Enfants de la Creuse”—approximately 1,600 children from Réunion, sent to the less populated areas in France in 1963-1982, with no hope of return, on the orders of the then prefect of Réunion Michel Debré—exploded in the media in 2002 after a long period of collective amnesia on the subject. The life stories of Jean-Jacques Martial and Jean-Pierre Gosse were an essential contribution to the sudden remembering of what happened. They were followed by novels, among which Jean Louis Robert’s Creuse, ta tombe, which completely deconstructs the history of Réunion in order to create echoes between the different enslavement Systems known in the island. In order to tell the story of the children, the texts in fact focus on a twofold paradigmatic diversion: deportation and slavery. These two references once more deprive the children of the uniqueness of their experience. Yet at the same time they contribute to the construction of an “exemplary memory” in Réunion.